Design and validation of recombinant protein standards for quantitative Western blot analysis of cannabinoid CB1 receptor density in cell membranes: an alternative to radioligand binding methods - Saumell-Esnaola, Miquel; Elejaga-Jimeno, Ainhoa; Echeazarra, Leyre; Borrega-Román, Leire; Barrondo, Sergio; López de Jesús, Maider; González-Burguera, Imanol; Gómez-Caballero, Alberto; Goicolea, María Aranzazu; Sallés, Joan; García del Caño, Gontzal (Microbial cell factories, 2022)
Background Replacement of radioligand binding assays with antibody-antigen interaction-based approaches for quantitative analysis of G protein-coupled receptor (GPCR) levels requires the use of purified protein standards containing the antigen. GPCRs in general and cannabinoid CB 1 receptor in particular show a progressive tendency to aggregate and precipitate in aqueous solution outside of their biological context due to the low solubility that the hydrophobic nature imprinted by their seven transmembrane domains. This renders full-length recombinant GPCRs useless for analytical purposes, a problem that can be overcome by engineering soluble recombinant fragments of the receptor containing the antigen. Results Here we generated highly soluble and stable recombinant protein constructs GST-CB1 414–472 and GST-CB1 414-442 containing much of the human CB 1 receptor C-terminal tail for use as standard and negative control, respectively, in quantitative Western blot analysis of CB 1 receptor expression on crude synaptosomes of the adult rat brain cortex. To this end we used three different antibodies, all raised against a peptide comprising the C-terminal residues 443–473 of the mouse CB 1 receptor that corresponds to residues 442–472 in the human homolog. Estimated values of CB 1 receptor density obtained by quantitative Western blot were of the same order of magnitude but slightly higher than values obtained by the radioligand saturation binding assay. Conclusions Collectively, here we provide a suitable Western blot-based design as a simple, cost-effective and radioactivity-free alternative for the quantitative analysis of CB 1 receptor expression, and potentially of any GPCR, in a variety of biological samples. The discrepancies between the results obtained by quantitative Western blot and radioligand saturation binding techniques are discussed in the context of their particular theoretical bases and methodological constraints.